A Study of Socio- Cultural factors and their influence on Rural Women Empowerment in Solar Power Sector in select states of India - Kumari, A.Padma Yasoda; Shankar, Dr. A. Udaya (The journal of contemporary issues in business and government, 2021)
Rural women’s participation in the formal economy is small and largely confined to domestic work and less payed low grade jobs in the economy due to social, economic, political and other factors. Therefore, this study is done to assess the socio cultural factors that influence the rural women empowerment in Solar Power Sector in select states of India. Basically, the study is exploratory in nature. Primary as well as secondary data is used for the study while including the Quantitative and qualitative techniques. For this study, 500 rural women respondents who were into solar business were taken from the states of Andhra Pradesh, Bihar, Orissa and Telangana. A structured questionnaire was used for data collection. Descriptive statistics was used to analyze the data collected. Also, SPSS software was used to further analyse the data. The findings of study revealed that the majority of the rural women respondents were interested to start the solar business. From the data it is further observed the socio-cultural attitudes of the rural women like: Social Empowerment- Participation in domestic decision making, Recognition in the society, Access to and visibility in Social spaces, Rural women and Political attitudes- Ability to exercise right to vote, Rural women and Psychological attitudes- Self- esteem. Thus, it is suggested that the government of India and other NGO’s should work together to bolster the rural women’s socio-cultural development by providing required skills training, diversification sources of women income, guidance with the procedures to procure the loans, creating business networks and so on.